Class B CpG-ODN2006 is highly associated with IgM and antimicrobial peptide gene expression through TLR9 pathway in yellowtail Seriola lalandi. Issue 77 (June 2018) - Angulo, Carlos; Alamillo, Erika; Hirono, Ikuo; Kondo, Hidehiro; Jirapongpairoj, Walissara; Perez-Urbiola, Juan Carlos; Reyes-Becerril, Martha
Abstract: The purpose of this study was to characterize the TLR9 gene from yellowtail ( Seriola lalandi ) and evaluate its functional activity using the class B Cytosine-phosphate-guanine-oligodeoxynucleotide2006 (CpG-ODN2006) in an in vivo experiment after one-week immunostimulation. The gene expressions of TLR9, Immunoglobulin M (IgM), antimicrobial peptides and cytokines were evaluated by real time PCR, and humoral immune parameters were analyzed in serum. The TLR9 nucleotide sequence from yellowtail was obtained using the whole-genome shotgun sequencing method and bioinformatics tools. The yellowtail full-length cDNA sequence of SlTLR9 was 3789 bp in length, including a 66-bp 5′-untranslated region (UTR), a 3′-UTR of 528 bp, and an open reading frame (ORF) of 3192 bp translatable to 1064 amino acid showing a high degree of similarity with the counterparts of other fish species and sharing common structural architecture of the TLR family, including LRR domains, one C-terminal LRR region, and a TIR domain. Gene expression studies revealed the constitutive expression of TLR9 mRNA in all analyzed tissues; the highest levels were observed in intestine, liver and spleen where they play an important role in the fish immune system. The expression levels of TLR9 after B class CpG-ODN2006 (the main TLR9-agonist) was significantly up-regulated in all analyzed tissues, with the high expression observed in spleen followed by intestine and skin. The CpG-B has been shown as a potent B cell mitogen, and interestingly, IgM mRNA transcript was up-regulated in spleen and intestine, which was highly correlated with TLR9 after CpG-ODN2006 stimulation. The antimicrobial peptides, piscidin and NK-lysine, were up-regulated in spleen and gill after CpG-ODN2006 injection with a high correlation ( r ≥ 0.82) with TLR9 gene expression. Cytokine genes were up-regulated in spleen, intestine and skin after CpG-ODN was compared with the control group. No significant correlation was observed between TLR9 and IL-1β, TNF-α and Mx gene expressions. The results showed that CpG-ODN2006 intraperitoneal injection enhanced lysozyme, peroxidase and superoxide dismutase activities in serum and demonstrated that CpG-ODN2006 can induce a specific immune response via TLR9 in which IgM and antimicrobial peptides must have an important role in the defense mechanisms against infections in yellowtail. Highlights: TLR9 functional architecture from Seriola lalandi was characterized in silico. TLR9 gene expression was highly up-regulated in spleen and intestine by CpG ODN2006. CpG-ODN2006 up-regulates IgM, antimicrobial peptides and cytokines genes. CpG-ODN2006 induce a high correlation of IgM and antimicrobial peptides genes through the TLR9 pathway. Antioxidant and immune parameters in serum enhanced in CpG-ODN2006 group.